2020
DOI: 10.3389/fsufs.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

The Soybean Trap: Challenges and Risks for Brazilian Producers

Abstract: Since the 1970s, Brazilian soybean production has grown rapidly, driven by increasing national and international demand and rising prices. Consequently, soybean production has come to be perceived as an attractive opportunity, with the number of farms producing soybean across the country reaching around 240,000 in 2017. However, producers can become trapped by dependencies on moneylenders, traders and input supply companies, facing so-called' agricultural treadmills'. In this study we undertook interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…Previous literature has called attention to the need of achieving synergies, and minimizing trade-offs, between SDGs related to food systems [3]. Farm size and production, along with numerous other agricultural-socioeconomic measures, are key indicators for understanding the sustainability of food systems [4,5]. However, greater understanding is needed about when, where, and in which situations large or small farms can achieve better production outcomes, and improved synergies considering production, environment, and economy [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous literature has called attention to the need of achieving synergies, and minimizing trade-offs, between SDGs related to food systems [3]. Farm size and production, along with numerous other agricultural-socioeconomic measures, are key indicators for understanding the sustainability of food systems [4,5]. However, greater understanding is needed about when, where, and in which situations large or small farms can achieve better production outcomes, and improved synergies considering production, environment, and economy [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rada and Fuglie [4] suggested that farm size and productivity evolve with the stages of economic development in a region and that there is no single economically optimal agrarian structure. However, the logic of economies of scale has driven increased production to favor larger farms in many places [5] and leading regions to specialize in specific commodity products to gain competitive advantages. This increased production and specialization has been traded-off against other agricultural socioeconomic benefits (e.g., lowering rural labor demand and crop diversity) and environmental degradation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations